Relations between indoor rehabilitation and basic health services in a developing country - Uddin, Taslim; Ahmed, Badrunnessa; Shoma, Farzana Khan (Frontiers in Rehabilitation Sciences, 2023)
Background and Introduction: Physical rehabilitation is vital for patients to regain maximum function, and many admitted patients require a period of comprehensive rehabilitation in an indoor facility. Approximately 80% of people with a disability live in developing countries and lower-middle-income countries face multiple challenges in rehabilitation. The physical Medicine and Rehabilitation (PMR) inpatient unit at Bangabandhu Sheikh Mujib Medical University (BSMMU) was established in June 2015. Inpatient rehabilitation care is provided by a team of skilled professionals under the leadership of a rehabilitation physician and can help achieve the best possible outcome by preventing complications, facilitating recovery, and lowering healthcare costs. The goal of the study: To conduct an analysis of indoor rehabilitation programs in a developing country based on the demographics and medical conditions of the admitted patients. Ultimately, this will prognosticate functional outcomes, set rehabilitation goals, and administer rehabilitation therapy modalities. and facilitate discharge planning. Methods: This cross-sectional study was done in the PMR inpatient rehabilitation ward of Bangabandhu Sheikh Mujib Medical University (BSMMU) in Dhaka city during the period of June 2015 to December 2019. Demographic and clinical data were obtained by means of a retrospective medical record review utilizing a standardized data extraction form. Results: The male-to-female ratio among the 1309 admitted patients was 10:7, with the majority of 411 (31.4 percent) cases falling between the ages of 46 and 60yrs. Rehabilitation outpatient department (OPD) was the most common mode of admission (78%), and the majority of patients (60.8%) were discharged home after intensive rehabilitation. A large number of patients absconded and were prematurely discharged from the facility. There was a large amount of missing data and absconded patients about their clinical conditions and mode of disposal, with a maximum number (34.4%) of patients staying at the hospital for 15–21 days. Musculoskeletal and neurological conditions represented the maximum number (79.8%) of admissions, and there was a lower number of admissions with post-traumatic and other rehabilitation conditions. Conclusions: This study provided an overview of inpatient rehabilitation in an LMIC setting, which might be useful for setting rehabilitation goals and administering rehabilitation therapy modalities. and facilitate discharge planning.